PENERAPAN SISTEM MANAJEMEN KEBAKARAN DI PT. ADILUHUNG SARANASEGARA INDONESIA, BANGKALAN - Ranggi Nugraha (Universitas Airlangga, 2018)
PT. Adiluhung Saranasegara Indonesia, Bangkalan are ship building and ship repair industry. This company has high risk of fire. This company used LPG for cutting the iron plate process and making new vessels. Based on the the fire triangle theory, a fire could occur if there is an element of fuel, oxygen and heat. An element of fuel which can cause a fire include solids, liquids and gases. This research aims were to identify the management systems of fire in PT. Adiluhung Saranasegara Indonesia, Bangkalan which includes pre-fire program and currently fire. This study applied descriptive study using cross-sectional approach. There were fifteen informants took part in this study that consisted of head officer, safety officer, health safety and environment (HSE) staff, firemans and securities. Data were collected by conducting interviews, observations, and document reviews. Content and data analysis were used and presented in the form of narration. The results showed that all the pre-fire program (policies in management, organization, and procedures; the identification of the risks of fire, development and training, active and passive protections towards the incidence of fire, fire inspection, the prevention of damages) has been carried out. On-fire program also have emergency respons team. Keywords: during a fire, pre fire, shipping industry